Marketing information system in the agricultural service. (Journal of Economic Research & Business Administration, 2016)
The article is devoted to questions of effective management in the field of agribusiness. It is known that the efficiency of agromarketing and the quality of management decisions largely depend on the competent performance of a marketing information system. Therefore, making the right decisions depends primarily on the selection of the necessary useful information and the quality of its analysis. This requires the development of specific marketing information system. The authors considered the process of agro marketing research, namely: identifying the problems and formation of research objectives, selection of information sources, the formation of agro marketing plan research, collect data, report on the results obtained. In this article the special interest is given to competitors of the farmers, which allows time to change strategy and tactics, and to develop a system of measures to protect the enterprise’s position in the market. The authors consider general approaches to marketing management, particularly, marketing information system in agriculture, as the basis for reducing risks when making and implementing management decisions.
Keywords: agribusiness; agro marketing information; subsystem; reporting; strategy; tactics; planning; strategic plan; risk analysis; opportunities for companies; target market.